Pelaksanaan Edukasi Kesehatan Tentang Penyakit Hipertensi - Qamarya, Nurul; Purwoto, Ady; Prabu Aji, Sulistyani; Hartaty, Hartaty; Kurni Menga, Maria (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Community guidance aimed at increasing people's knowledge and attitudes in preventing hypertension. Based on the results of community diagnoses, there are still many people who are affected by hypertension. In addition, the information obtained shows that there is still insufficient public knowledge about hypertension. Methods used in education; planning and preparation in the form of licensing, as well as inviting target communities; implementation and process in the form of presentation of materials and closing; Monitoring and evaluation, monitoring of this program is by always strengthening the knowledge and attitudes of the community, the evaluation of this program can be seen from increasing the knowledge and attitudes of the community. The results of the counseling showed an increase in knowledge about hypertension. Healthcare and public health center can help the community by counseling about hypertension and paying attention to their health, especially the problem of hypertension